Bisphosphonate Risks: Knowledge and Attitudes Among Dentists in Ecuador - Perero, Leslye Arianna Castañeda; Almache, Angela Mercedes Murillo; Solorzano, Francisco Xavier Vera; Coronel, Jenny Nathaly Pico; Posligua, María Patricia Lin; Intriago, Ana Cristina Castro; Cedeño, Ketty Andreina Pinargote (Journal of Posthumanism, 2025)
Bisphosphonates are pharmacological agents used in patients with bone disorders, as they inhibit the activity of cells responsible for bone resorption, thereby contributing to the strengthening of bone tissue. Despite their benefits, their use involves risks that may impact dental practice. This study aims to determine the level of knowledge and attitudes of dentists in the city of Portoviejo, Ecuador, regarding the risks associated with patients undergoing bisphosphonate treatment. The sample consisted of 148 dentists from Portoviejo, Ecuador, selected through non-probability convenience sampling. A validated questionnaire was applied, with a content validity measured by Aiken’s V coefficient of 0.98 and a Cronbach’s alpha reliability of 0.874. More than half of the dentists (50.7%) demonstrated a high level of knowledge. Attitudes were generally favorable, particularly concerning the avoidance of invasive surgical procedures. A discrepancy between self-reported knowledge and clinical practice was observed. Specialized training and recent continuing education had a positive influence on the results. Continuous education is recommended to be reinforced.